Novelties in Lippia (Verbenaceae) from Minas Gerais State, Brazil - Cardoso, Pedro Henrique; Valério, Vanessa Imaculada Dos Reis; Neto, Luiz Menini; Trovó, Marcelo; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2020)
We describe Lippia krenakiana, a new species of Verbenaceae endemic to the campos rupestres of Espinhaço Range in Minas Gerais, Brazil. The species is mainly distinguished by the combination of ovate-deltoid leaf blades and sericeous-villous indument with sessile and pedicellate glandular trichomes. We provide a diagnosis, a morphological comparison with the most similar species, a distribution map, preliminary conservation assessment, and photos of live specimens. Additional notes on Lippia are also provided, as we designate lectotypes for L. glazioviana and L. diamantinensis, and L. violacea is proposed as a new synonym for L. rubella.